Association of major depressive disorder with chronic diseases and multimorbidity in Brazilian adults, stratified by gender: 2019 National Health Survey - Neuciani Ferreira da Silva Sousa; Marilisa Berti de Azevedo Barros; Lhais de Paula Barbosa Medina; Deborah Carvalho Malta; Celia Landmann Szwarcwald
ABSTRACT: Objective: To analyze the association of major depressive disorder with chronic non-communicable diseases and multimorbidity in Brazilian adults, stratified by gender, as well as examine the interaction between gender and chronic non-communicable diseases in association with major depressive disorder. Methods: Based on a sample of 65,803 adults from the 2019 National Health Survey, we estimated the prevalence of major depressive disorder (≥10 points in the Patient Health Questionnaire) according to the presence of chronic non-communicable diseases and multimorbidity (≥2 chronic diseases). Prevalence ratios and their respective confidence intervals were calculated by Poisson regression, and multiplicative interaction terms were used to assess the role of gender in the associations. Results: The prevalence of major depressive disorder among Brazilian adults (18-59 years) was 10.9%, with a statistically significant difference between men (6.0%) and women (15.4%) (p<0.001). Individuals with any chronic non-communicable disease and multimorbidity showed a higher prevalence of major depressive disorder, both in the general population and in each gender. However, the association of major depressive disorder with chronic non-communicable diseases tended to be stronger among men. Data also showed an interaction between the male gender and multimorbidity or specific diseases, such as arthritis or rheumatism, heart disease, and chronic kidney disease, in association with major depressive disorder. Conclusion: The results reveal a significant association between major depressive disorder and chronic non-communicable diseases in both genders and raise the hypothesis that the effects of multimorbidity and certain diseases may be greater on the mental health of men.